Sūrya Devatā : Vaidika aura Vedottara Saṃskr̥ta Sūryastutiyoṃ meṃ - Tivārī, Śaśi. (Naī Dillī : Meharacanda Lachamanadāsa Pablikeśansa, 1994)
Comprehensive study on the cult of Sūrya (Hindu deity), as depicted in Hindu scriptures.
In Hindi; includes passages in Sanskrit.
Includes bibliographical references (p. 297-308) and index.
Mode of access: Internet.
Keywords: Sūrya -- (Hindu deity) -- Cult